Radionuclide concentrations in medicinal florae and committed effective dose through Ayurvedic medicines - Monica, S.; Jojo, P. K.; Khandaker, Mayeen Uddin * (Taylor & Francis, 2020)
Purpose: Ayurveda is one of the oldest systems of medicines in the world being practiced widely in the Indian subcontinent for more than 3000 years, and still remains as one of the important traditional health care systems. The Ayurvedic drugs are derived primarily from various parts of the plants, like root, leaf, flower, fruit or plant as a whole. Plants uptake minerals and other nutrients from the soil through their root system. Along with other minerals radionuclides present in the growing media also reach to the plant parts following the same pathway. Realizing the probable health hazards via the intake of Ayurvedic drugs, it is important to assess the concentration of natural radionuclides in commonly used medicinal plants. Materials and methods: NaI(Tl) scintillator-based gamma-ray spectrometry has been used to determine the activity concentrations of primordial radionuclides (226Ra, 232Th and 40K) in the most commonly used medicinal plant parts as ingredients of Ayurvedic medicines in India. Results and discussion: The average specific activity (Bqkg−1) of 226Ra, 232Th and 40K was found to be 43 ± 18, 36 ± 15 and 230 ± 46, respectively. The estimated annual committed effective doses due to the intake of common Ayurvedic medicines at prescribed dosage was found to be 39 ± 16 µSv y−1, which is quite low as compared with the radiation dose limit of 1 mSvy−1 from all natural sources, reported by the International Commission on Radiological Protection (ICRP-60). Conclusions: It is found categorically that intake of Ayurvedic medicines at normal dosage poses no radiological hazard to the individual. Present results are significant in the wake of myths that many hazardous materials including radioisotopes are present at higher levels. Obtained results also serve as a reference information for the distribution of radionuclides in medicinal plant species.